The Role of Needs Analysis and Learner Differences in Language Learning - Dilobarxon Berdiali Qizi Azimova (International Journal on Integrated Education, 2022)
This paper investigates the necessity of needs analysis and learning styles in foreign language learning namely English and presents the findings of small scale research to contribute teaching and learning.